Unilateral Spinal Anesthesia with Hypobaric Bupivacaine for Outpatient Knee Arthroscopy - رقماني نجوى (Latakia University Journal -Medical Sciences Series, 2021)
Aims: Study the unilateral spinal anesthesia with hypobaric Bupivacaine for outpatient knee arthroscopy; its effectiveness, success, side effects, time of sensory and motor block resolution, and patient’s satisfaction with the anesthesia, in comparison with conventional spinal anesthesia. Methods: 50 patients were randomized into two groups: Group U: Unilateral spinal anesthesia with 2.5ml Hypobaric Bupivacaine 0.5% in lateral decubitus with the limb to be operated facing upwards. Group C: Conventional spinal anesthesia with 2.5ml Isobaric Bupivacaine 0.5% in setting position. Level of motor and sensory block, arterial pressure, pulse, need for intravenous solution or vasopressors and complications were evaluated and compared between the groups in many times of surgery, time of sensory and motor block resolution, and patient’s satisfaction were evaluated after surgery. Results: Spinal block succeeded in all patients in group U in the operated sides with a Bromage score iii and iv, the non-operated sides were not blocked, no patient in group U required analgesia or additional anesthesia, while the spinal block failed in two patients in group C and a general anesthesia was performed. Sensory block on operated sides were significantly higher in group C (T4-T6) vs. (T10-T12) in group U; more hypotension, fluids and vasopressors were required in group C, while no vasopressor was required in group U. mean regression times of sensory and motor block were significantly faster in group U )130±17 & 100±15( minutes vs. (250±19 & 195±23) min in group C. Patient’s satisfaction was higher in group U: 96% vs. 74% in group C. Conclusion: Hypobaric bupivacaine in the lateral position provides successful unilateral block in 100% of patients, it provides stability hemodynamic and requires less fluids and vasopressors, it has the satisfaction and good evaluation of patients, which makes it a better choice as a new alternative to conventional spinal anesthesia for outpatients knee arthroscopy, and allows patients to be discharged on the same day of surgery because of short time of sensory and motor block.